2015
DOI: 10.1016/j.jmaa.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Gevrey regularity for integro-differential operators

Abstract: We prove for some singular kernels K(x, y) that viscosity solutions of the integro-differential equation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…
We prove that for a certain class of kernels K(y) that viscosity solutions of the integro-differential equationare locally analytic if f is an analytic function. This extends results in [1] in which it was shown that such solutions belong to certain Gevrey classes.
…”
supporting
confidence: 85%
“…
We prove that for a certain class of kernels K(y) that viscosity solutions of the integro-differential equationare locally analytic if f is an analytic function. This extends results in [1] in which it was shown that such solutions belong to certain Gevrey classes.
…”
supporting
confidence: 85%
“…The function N s α (x) then equals the series on the right-hand side of (3.15). In view of point (4) we thus see that, at least in the case α = s + n, N s α (x) is analytic with respect to x for |x| < 1 and, further, that the desired relation (3.9) holds.…”
Section: Boundary Singularity and Diagonal Form Of The Single-intervamentioning
confidence: 67%
“…For the case r = 1/2, L α 1/2 represents the integral fractional Laplacian operator [2]. The existence, uniqueness and regularity of the solution to the fractional Laplacian equation has been investigated by a number of authors, in R 1 see [3], in R n≥2 [4,11,19,31]. Recently the regularity results for the fractional Laplacian equation was extended by Hao and Zhang in [22,38] Fewer results on the regularity of the solution to the general fractional diffusion, advection, reaction equation have been established.…”
Section: Introductionmentioning
confidence: 99%
“…In the next section we present some preliminary definitions and results. Sections 3,4, and 6 present the three different (but equivalent) definitions of the weighted Sobolev spaces. Section 4 also establishes some useful properties of the space H s (a,b) (I).…”
Section: Introductionmentioning
confidence: 99%